Exploring english lexical bundles in the methodology chapter of education doctoral theses - Yusob, Khairul Firhan; Mohd Afandi, Mohamad Iqbal Afham; Zaini, Muhammad Harriz; Abdul Aziz, Roslina (GADING Journal for the Social Sciences, 2024)
Lexical bundles (LB) refer to sequences of words that frequently co-occur in texts. While numerous studies on LB have been conducted in various sections of theses, such as abstracts, acknowledgements, introductions, findings, and conclusions, the Methodology chapter has received comparatively less attention, despite its crucial role in outlining the research process. To address this gap, the present study aims to analyse the use of English LB in the Methodology sections of 50 PhD theses from the Education domain. The results reveal that commonly used bundles in the corpus often serve to frame and situate the studies, as evidenced by bundles such as in this study, for the purpose of, and in the context of. Furthermore, analysis of the structures discovers noun phrase bundles occur most frequently, followed by prepositional and verb phrases. In terms of the LB functions, Research oriented bundles are predominant, followed by text- and participant-oriented bundles. These findings are valuable not only for PhD candidates in Education but also for postgraduate students, as they provide insight into common academic phrases used in the Methodology sections of theses.